1984
DOI: 10.1620/tjem.144.129
|View full text |Cite
|
Sign up to set email alerts
|

A case of insulin resistance associated with acanthosis nigricans.

Abstract: We described here a 12-year-old male patient with the syndrome of insulin resistance and acanthosis nigricans type A. Insulin levels at fasting state and after glucose loading were 149 + 63 ,uU/ml (mean± S.D.) and over 1,000 pU/ml respectively, while the fasting level of blood glucose was 77.7+8.9 mg/ml (mean+s.D.). A marked resistance to exogenous insulin was observed. Circulating levels of insulin antagonists such as growth hormone, cortisol and glucagon were within the normal range. Proinsulin was less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…These abnormalities are consistent with data from several studies showing both impaired insulin-receptor autophosphorylation [25 -27] and reduced numbers of insulin receptors in subjects with AN [13,28]. Although obesity has been found in some, but not all, studies to be associated with down-regulation of insulin receptors [29] and diminished intracellular signaling [30], obesity is unlikely to be solely responsible for the insulin resistance seen in subjects with AN [28]. In fact, 4 of our 5 subjects with AN reported that AN appeared before the presence of extreme obesity, suggesting insulin resistance and hyperinsulinemia preceded the development of extreme obesity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These abnormalities are consistent with data from several studies showing both impaired insulin-receptor autophosphorylation [25 -27] and reduced numbers of insulin receptors in subjects with AN [13,28]. Although obesity has been found in some, but not all, studies to be associated with down-regulation of insulin receptors [29] and diminished intracellular signaling [30], obesity is unlikely to be solely responsible for the insulin resistance seen in subjects with AN [28]. In fact, 4 of our 5 subjects with AN reported that AN appeared before the presence of extreme obesity, suggesting insulin resistance and hyperinsulinemia preceded the development of extreme obesity.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, defects in insulin binding [21] and post-insulin receptor function [22], and genetic defects within the insulin receptor gene have been documented in patients with AN [23,24]. These abnormalities are consistent with data from several studies showing both impaired insulin-receptor autophosphorylation [25 -27] and reduced numbers of insulin receptors in subjects with AN [13,28]. Although obesity has been found in some, but not all, studies to be associated with down-regulation of insulin receptors [29] and diminished intracellular signaling [30], obesity is unlikely to be solely responsible for the insulin resistance seen in subjects with AN [28].…”
Section: Discussionsupporting
confidence: 88%